Práticas colaborativas e escola inclusiva: uma experiência de outros tempos e espaços escolares - Mattana, Dinara Patrícia (2023)
The inclusive school finds in collaborative practices the possibility of reinvention. As object/theme of investigation, this dissertation takes the training process and the constitution of collaborative practices in a perspective of inclusive school, developed and inserted in the production of the Graduate Program in Public Policy and Educational Management and the Study and Research Group in Special Education and Inclusion - GEPE/UFSM. The challenge of the research was to seek to understand and analyze scenes from a cycle of training and its characteristics as collaborative practices in school places and times of a school that is being produced in an inclusive perspective, a goal that was led by the problem: How to operacionalize a cycle of collaborative practices in the perspective of the constitution of an inclusive school? What characteristics constitute collaborative practices in inclusive schools? Methodologically, the research was constituted in qualitative research with inspiration in the narrative and implicit perspective, considering that it emerges from the experience built in a cycle of collaborative practices in a Basic Education School of the Municipal Public Network of the city of Santo Ângelo/RS. For the analysis of school scenes, categories were built to identify the scenes related to the field of information and/or experience to which they belonged and analyze them from the perspective of place and school time that it was possible to produce in such a scene. The scenes in which they were analyzed, were part of the record of the researcher who, between the years 2019 and 2021, with her colleagues, could live the experience with the collaborative practices for the reinvention of the school with the quality of being inclusive. It was concluded that collaborative practices are generated in the details of encounters and events in which people are involved with the accidental, random, improbable, circumstantial, singular, and temporal. Furthermore, as a result, an educational product of the social technology type is presented, entitled "Operationalization and characterization of collaborative practices in inclusive schools", to expand the senses and meanings of collaborative practices in schools, as well as to indicate the possibilities of operationalizing and characterizing them.